A Review of SARS-CoV2: Compared With SARS-CoV and MERS-CoV - Huan Zhou; Huan Zhou; Huan Zhou; Junfa Yang; Chang Zhou; Bangjie Chen; Hui Fang; Shuo Chen; Xianzheng Zhang; Linding Wang; Lingling Zhang (Frontiers in Medicine, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) has been spreading rapidly in China and the Chinese government took a series of policies to control the epidemic. Studies found that severe COVID-19 is characterized by pneumonia, lymphopenia, exhausted lymphocytes and a cytokine storm. Studies have showen that SARS-CoV2 has significant genomic similarity to the severe acute respiratory syndrome (SARS-CoV), which was a pandemic in 2002. More importantly, some diligent measures were used to limit its spread according to the evidence of hospital spread. Therefore, the Public Health Emergency of International Concern (PHEIC) has been established by the World Health Organization (WHO) with strategic objectives for public health to curtail its impact on global health and economy. The purpose of this paper is to review the transmission patterns of the three pneumonia: SARS-CoV2, SARS-CoV, and MERS-CoV. We compare the new characteristics of COVID-19 with those of SARS-CoV and MERS-CoV.